Specification and epigenomic resetting of the pig germline exhibit conservation with the human lineage - Zhu, Qifan (Cell Rep, 2021)
Investigations of the human germline and programming are challenging because of limited access to embryonic material. However, the pig as a model may provide insights into transcriptional network and epigenetic reprogramming applicable to both species. Here we show that, during the pre- and early migratory stages, pig primordial germ cells (PGCs) initiate large-scale epigenomic reprogramming, including DNA demethylation involving TET-mediated hydroxylation and, potentially, base excision repair (BER). There is also macroH2A1 depletion and increased H3K27me3 as well as X chromosome reactivation (XCR) in females. Concomitantly, there is dampening of glycolytic metabolism genes and re-expression of some pluripotency genes like those in preimplantation embryos. We identified evolutionarily young transposable elements and gene coding regions resistant to DNA demethylation in acutely hypomethylated gonadal PGCs, with potential for transgenerational epigenetic inheritance. Detailed insights into the pig germline will likely contribute significantly to advances in human germline biology, including in vitro gametogenesis.